1992
DOI: 10.1111/j.1365-2869.1992.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of evening bright light exposure on melatonin, body temperature and sleep

Abstract: SUMMARY Five male subjects were exposed to a single 2-h period of bright (2500 lux) or dim ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Contradictory findings have been reported in bright light studies in which both temperature and sleep were assessed. Bunnell et al (1992) found a steeper decline in tympanic and rectal temperature following exposure to bright light in the evening; the decline was associated with increased EEG slow-wave activity and a nonsignificant reduction in sleep latency. However, Cajochen et al (1992) reported increased rectal temperature and sleep latency, as well as attenuated EEG slow-wave activity after late night bright light exposure.…”
Section: Effects On Sleep Of Changes In Thermoregulation and Body Andmentioning
confidence: 92%
“…Contradictory findings have been reported in bright light studies in which both temperature and sleep were assessed. Bunnell et al (1992) found a steeper decline in tympanic and rectal temperature following exposure to bright light in the evening; the decline was associated with increased EEG slow-wave activity and a nonsignificant reduction in sleep latency. However, Cajochen et al (1992) reported increased rectal temperature and sleep latency, as well as attenuated EEG slow-wave activity after late night bright light exposure.…”
Section: Effects On Sleep Of Changes In Thermoregulation and Body Andmentioning
confidence: 92%
“…Deterioration of circadian rhythms in elderly is thought to contribute to sleep disturbances and reduced daytime functioning, and finding ways in which to improve the circadian timing system may therefore be of interest for the well-being of elderly (Van Someren et al, 1993a). Bright light, the primary modulator of the circadian timing system, is indeed effective both in increasing vigilance (Badia et al, 1991;Campbell and Dawson, 1990) and in improving subsequent sleep (Bunnell et al, 1992;Campbell et al, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…In humans, melatonin taken in the early evening, which has clock-shifting effects similar to light exposure in the early morning (eastward travel), REM duration increases independently of changes in NREM sleep 66. When traveling in the opposite direction and the clock is delayed, there is an increase in REM sleep latency 67. This effect could be due to an increase in SWA and other components of NREM sleep that are associated with rebound to sleep deprivation, and REM might later show a compensatory rebound on subsequent nights.…”
Section: Transient Disruption Of the Circadian System: Jet Lagmentioning
confidence: 99%